2011
DOI: 10.1007/s00251-011-0537-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of full-length MHC class II sequences in Indonesian and Vietnamese cynomolgus macaques

Abstract: In recent years, the use of cynomolgus macaques in biomedical research has increased greatly. However, with the exception of the Mauritian population, knowledge of the MHC class II genetics of the species remains limited. Here, using cDNA cloning and Sanger sequencing we identified 127 full-length MHC class II alleles in a group of 12 Indonesian and 12 Vietnamese cynomolgus macaques. Forty-two of these were completely novel to cynomolgus macaques while 61 extended the sequence of previously identified alleles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
3
19
0
1
Order By: Relevance
“…Of these, 73 alleles were mismatched at one or more bases from any sequences in the database of named alleles, 44 were extensions to previously identified named alleles, and only 11 matched named full-length sequences. Almost half of these sequences (61 of 128) are identical to alleles previously described in rhesus and/or cynomolgus macaques, which is consistent with previously observed sharing of pig-tailed macaque MHC class I sequences and high levels of MHC class II allele sharing between macaque species (Lafont et al 2004; Doxiadis et al 2006; O’Leary et al 2009; Creager et al 2011). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Of these, 73 alleles were mismatched at one or more bases from any sequences in the database of named alleles, 44 were extensions to previously identified named alleles, and only 11 matched named full-length sequences. Almost half of these sequences (61 of 128) are identical to alleles previously described in rhesus and/or cynomolgus macaques, which is consistent with previously observed sharing of pig-tailed macaque MHC class I sequences and high levels of MHC class II allele sharing between macaque species (Lafont et al 2004; Doxiadis et al 2006; O’Leary et al 2009; Creager et al 2011). …”
Section: Resultssupporting
confidence: 89%
“…In this survey, we performed full-length MHC-II allele discovery for the DRA , DRB , DQA , DQB , DPA , and DPB loci in 32 pig-tailed macaques using a novel next-generation sequencing method. This method is faster and higher-throughput than traditional cloning and Sanger-based sequencing methods, facilitating more rapid full-length MHC-II allele discovery (Creager et al 2011; Karl et al 2009). We also performed an exon 2-based genotyping assay to validate the full-length sequencing results with an independent set of primers specific for the DRB , DQA , DQB , DPA , and DPB loci.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is also observed for the DPB1 locus studied in different non-human primates, and, as discussed previously, alleles discovered for this locus are numbered sequentially. In particular, rhesus and crab-eating/cynomolgus macaques have been studied extensively in recent years for their DPB1 locus, and 26 and 57 different alleles have been deposited in the IPD-MHC NHP database, respectively (Aarnink et al 2011; Creager et al 2011; Doxiadis et al 2006; Giraldo-Vela et al 2008; Hashiba et al 1993; Ling et al 2011; O’Connor et al 2007; Otting et al 1998; Sano et al 2006; Slierendregt et al 1995). As expected, phylogenetic analyses have demonstrated that there is little sharing of Mhc-DPB1 lineages between humans and NHP.…”
Section: Current Implemented Nomenclature Revisions For Non-human Primentioning
confidence: 99%
“…The DR region of animals originating from Indochina and the Indonesian islands was recently described (Doxiadis et al 2010;Creager et al 2011;Doxiadis et al 2012).…”
Section: Introductionmentioning
confidence: 99%